Peningkatan pengetahuan dalam pencegahan terjadinya Bullying pada usia remaja - Ferasinta, Ferasinta; Rozani, Leni; Novitasari, Selvia; Padila, Padila; Sartika, Andry; Fitri Lina, Liza (JURNAL PENGABDIAN KESEHATAN, 2024)
Bullying is an aggressive act carried out continuously by one individual or group against another person who is physically, emotionally or socially weaker. These actions are often carried out with the aim of annoying, hurting, or dominating the victim. Bullying can occur in a variety of settings, including at school, the workplace, online environments, or in general society. Bullying can take many forms, including physical abuse such as beatings or physical attacks, verbal abuse such as taunts or threats, social abuse such as isolating or ostracizing someone, or online abuse such as sending insulting messages or posting derogatory content on social media. Bullying can also be direct, with the perpetrator taking action directly against the victim, or indirectly through spreading harmful rumors or gossip. The impact of bullying is very detrimental to the victim. They may experience mental health problems, including stress, anxiety, depression, and even thoughts of suicide. Victims of bullying may also experience a decline in academic performance, avoid school or work, and have difficulty building healthy social relationships. Prevention and handling of bullying is very important. Education about bullying awareness, development of social skills, and promotion of inclusive attitudes and respect for diversity can help reduce cases of bullying.